Caspase-1 Inhibition Impacts the Formation of Chondrogenic Nodules, and the Expression of Markers Related to Osteogenic Differentiation and Lipid Metabolism - Ramesova, Alice; Vesela, Barbora; Svandova, Eva; Lesot, Herve; Matalova, Eva (International journal of molecular sciences, 2021)
Caspase-1, as the main pro-inflammatory cysteine protease, was investigated mostly with respect to inflammation-related processes. Interestingly, caspase-1 was identified as being involved in lipid metabolism, which is extremely important for the proper differentiation of chondrocytes. Based on a screening investigation, general caspase inhibition impacts the expression of Cd36 in chondrocytes, the fatty acid translocase with a significant impact on lipid metabolism. However, the engagement of individual caspases in the effect has not yet been identified. Therefore, the hypothesis that caspase-1 might be a candidate here appears challenging. The primary aim of this study thus was to find out whether the inhibition of caspase-1 activity would affect Cd36 expression in a chondrogenic micromass model. The expression of Pparg, a regulator Cd36, was examined as well. In the caspase-1 inhibited samples, both molecules were significantly downregulated. Notably, in the treated group, the formation of the chondrogenic nodules was apparently disrupted, and the subcellular deposition of lipids and polysaccharides showed an abnormal pattern. To further investigate this observation, the samples were subjected to an osteogenic PCR array containing selected markers related to cartilage/bone cell differentiation. Among affected molecules, Bmp7 and Gdf10 showed a significantly increased expression, while Itgam, Mmp9, Vdr, and Rankl decreased. Notably, Rankl is a key marker in bone remodeling/homeostasis and thus is a target in several treatment strategies, including a variety of fatty acids, and is balanced by its decoy receptor Opg (osteoprotegerin). To evaluate the effect of Cd36 downregulation on Rankl and Opg, Cd36 silencing was performed using micromass cultures. After Cd36 silencing, the expression of Rankl was downregulated and Opg upregulated, which was an inverse effect to caspase-1 inhibition (and Cd36 upregulation). These results demonstrate new functions of caspase-1 in chondrocyte differentiation and lipid metabolism-related pathways. The effect on the Rankl/Opg ratio, critical for bone maintenance and pathology, including osteoarthritis, is particularly important here as well.
Keywords: Antigens, Differentiation; cartilage; Chondrocytes; Cell Differentiation; chondrocytes; chondrogeneze; Caspase Inhibitors; inhibition; Mice; Caspase 1; chondrocyty; lipid metabolism; Osteogenesis; diferenciační antigeny; osteogeneze; Lipid Metabolism; kaspasa 1; zvířata; Chondrogenesis; inhibitory kaspas; metabolismus lipidů; caspase-1; myši; buněčná diferenciace; osteoarthritis; Cd36; Animals